Penerapan Metode AHP-MAUT dan AHP-Profile Matching pada SPK Penempatan Siswa OJT - Gede Surya Mahendra; Eddy Hartono (Jurnal Teknik Informatika C.I.T Medicom, 2021)
To improve the quality and quality of employment, OJT is very much needed by Monarch Bali students, but the process, which is still manual, makes decisions that are taken less fast, accurate, effective and efficient. In line with the roadmap of Monarch Bali, it is necessary to develop an automation system to be able to improve the performance of decision making for OJT student placement by making a DSS. The method used in this research is AHP-MAUT and AHP-PM. The decision makers in this study were 3 people, and out of a total of 500 OJT students, 8 OJT students for F&B class, 12 OJT students for Housekeeping class, 13 OJT students for Catering class, and 17 OJT students for Food Management class with a total of 50 OJT students. In this study, AHP-MAUT and AHP-PM can be used properly and can be implemented into a web-based software which is quite user-friendly to users. Implementation of AHP-MAUT, OJT students from the Food Processing class with the code StudentD04 have the highest preference value of 0.5724, and OJT students from the F&B class with the code StudentA02 have a preference value of 4.1155 calculated using AHP-PM, each being ranked first.